EKSISTENSI DESA WISATA RELIGI BONGO DI MASA PANDEMIC COVID19 - sri sunarti; Desrika Talib (Tulisan Ilmiah Pariwisata (TULIP), 2021)
The purpose of the study was to describe the existence of a Religious Tourism Village during the Covid19 pandemic towards the best national tourist village. The research method used is descriptive qualitative with the main data sources being observation, in-depth interviews, and documentation. From the results of the study, it was found that Bongo Village as a Religious Tourism Village located in Gorontalo Regency has become the best Tourism Village at the National level, this is proof that the management of Bongo Village as a Religious Tourism village continues to be maximized despite experiencing several obstacles due to the impact of the COVID19 pandemic. The strategy taken is to always publish the uniqueness of the attraction and the cooperation between tourism managers and the community as well as government support, both central and local governments.